2019
DOI: 10.2478/pomr-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

New Designs of Centrifugal Magnetic Fluid Seals for Rotating Shafts in Marine Technology

Abstract: The centrifugal magnetic fluid seals have important advantage over the conventional centrifugal seals. They maintain very good sealing capacity at static, medium and high speeds of shaft rotation, with the increased seal lifetime, and minimum torque and static friction. These seals are particularly useful in cases when the angular shaft velocity varies and sometimes decreases to nearly or exactly zero, such as in flywheel applications, ship propeller main shafts, etc. Unique properties of the magnetic fluid gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Thus, the high interdisciplinary characteristics of magnetic fluids have brought experimental physicists, chemists, theoretical physicists, and applied mathematicians together. The magnetic fluids do constitute a rich source of application in hard disk scaling, 4 revolving X‐ray tubes for engineering applications, 5 revolving shafts sealing, 6 repair of retinal detachment in eye surgery, heat controlling in loudspeakers, 7 contrast agent in magnetic resonance imaging, 8 magnetic drug targeting, 9,10 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the high interdisciplinary characteristics of magnetic fluids have brought experimental physicists, chemists, theoretical physicists, and applied mathematicians together. The magnetic fluids do constitute a rich source of application in hard disk scaling, 4 revolving X‐ray tubes for engineering applications, 5 revolving shafts sealing, 6 repair of retinal detachment in eye surgery, heat controlling in loudspeakers, 7 contrast agent in magnetic resonance imaging, 8 magnetic drug targeting, 9,10 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-sliding stage, it can be assumed that θ ≈ 0, θ ≈ 0, z ≈ 0. So, according to (11), it can be concluded that…”
Section: Dynamic Parameter Identification Of Lugre Modelmentioning
confidence: 99%
“…In the past, many methods including filling felt oil rings or extruding U-shaped sealing rings in labyrinth structures were used [8], [9], [10], but both these examples cannot achieve a complete state of airtightness and water tightness. Moreover, they bring great friction interference torque to the servo control system, seriously affecting the low-speed stability and speed control accuracy of the detection system [11], which further affects the tracking accuracy of the target, and reduces the damage effect of the system's jammer or laser on the target.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al (2021) designed an FF seal for an aerospace air cylinder and solved the problem of leakage and service life. However, the performance of FF seals is restricted by their limited pressure capability per stage and intolerance of high temperature (Matuszewski, 2019). MRFs are composed of soft ferromagnetic or paramagnetic particles (about 1-10 μm) dispersed in a carrier fluid.…”
Section: Introductionmentioning
confidence: 99%